Electrical impedance myography (EIM) in a natural history study of C9ORF72 mutation carriers. Issue 5 (2nd July 2020) - Offit, Michelle B.; Wu, Tianxia; Floeter, Mary Kay; Lehky, Tanya J.
Abstract: Objective: Electrical Impedance Myography (EIM) was used to evaluate disease progression in subjects with C9ORF72 expansion mutations and to assess correlations with Medical Research Council (MRC) Scale and revised ALS Functional Rating Scale (ALSFRS-R) measurements. Four types of clinical presentations were assessed; Amyotrophic Lateral Sclerosis (ALS), Frontotemporal dementia (FTD) or other dementia, ALS-FTD, and asymptomatic (ASYMP). Methods: Subjects were divided into an ALS Group (ALS/ALS-FTD) and non-ALS Group (FTD/ASYMP) based on initial visit and evaluated at 0, 6, 18, and 30 months with EIM of 4 arm and 4 leg muscles, ALSFRS-R, and MRC scales. The change in EIM from baseline and correlation with the functional scale and strength testing were analyzed. Results: EIM 50kHz phase values significantly declined over time in the ALS group ( n  = 31) compared to the non-ALS group (FTD/ASYMP) ( n  = 19). In the ALS group, the decline in EIM was correlated with decline in the ALSFRS-R and MRC scores using within-subject correlations. Conclusion: In clinical trials with small populations of genetically associated ALS such as C9ORF -related ALS, EIM may be a useful quantitative biomarker. We did not detect decline in asymptomatic subjects, but longer term studies may detect early changes in this group.